Genetical and biochemical investigations on the regulation of cystein biosynthesis in Escherichia coli - Tully, M (1976)
This thesis is concerned with the mechanism by which the enteric bacterium Escherichia coli regulates its synthesis of the amino acid cysteine. The structural genes for the enzymes of the pathway are located at various positions around the chromosomes of both this organism and the closely related Salmonella typhimurium. Mutations in the cys B region of both organisms cause a deficiency of the cysteine biosynthetic enzymes. We concentrated our efforts on this region in E. coli. Previous work had shown that cys B mutations in E. coli were recessive to wild type and a scheme of positive control of cysteine biosynthesis via the cys B gene product(s) had been proposed. Genetical and nutritional analysis of the cys B region in Salmonella had indicated that it was complex, possibly containing three genes. Optimal conditions were found for a method of directed mutagenesis in E. coli using mutagenised transducing phage PI. This technique was then used to isolate 60 point mutants in the cys B region. Nutritional and genetical analyses confirmed that they lay in cys B. We isolated in addition a number of deletions extending into the cys B region of an E. coli F-prime carrying tho cys B and trp genes which had been inserted into S. typhimurium. These were used to construct a map and thus to order the point mutations into 16 deletion groups. Point mutations mapping at the extreme ends of the region were unable to complement one anorher. This result shows that there is only one gene in the cys B region. Nutritional data correlates with this conclusion. Some of the point mutants are temperature sensitive and in others the mutations are suppressed by the amber suppressor sup F: the gene therefore codes for a protein. Deletions ending in cys B and trp were isolated. We measured the rate of synthesis of enzymes of the tryptophan operon in strains carrying such deletionso In none of them was the expression of trp brought under cysteine-mediated control. We tentatively concluded that the cys B gene is transcribed in the direction trp → cys or, if it is transcribed in the direction cys → trp it is transcribed at a low, constant rate. We also sought constitutive mutations mapping in the cys B region. We isolated several mutants constitutive for at least part of the pathway: though the mutations conferring this phenotype were associated with the cys B region, they were unstable and their nature could not be elucidated. The results obtained in this thesis, together with recent work locating a partial constitutive mutation within the cys B region of Salmonella are strong evidence that cysteine biosynthesis in both organisms is indeed under positive control mediated via the cys B gene product.